Football is becoming boring; Network analysis of 88 thousands matches in 11 major leagues - Maimone, V; Yasseri, T (Cornell University, 2019)
Football is a major sport with worldwide popularity. In recent years excessive monetization of the game has been argued to have affected the quality of the match in different ways. In one hand playing football has become a high income profession and the players are highly motivated to perform well; on the other hand stronger teams have higher income and therefore they can afford better and more expensive players leading to even stronger appearance in tournaments that can make the game more imbalanced and hence predictable. In this work we take a data-heavy network science approach to measure predictability of football over 26 years in major European leagues. We benchmark our model against betting house predictions and after establishing its robustness we show that over time, the games in major leagues have become more predictable. We provide further support for this observation by showing that inequality between teams has increased in accord with the trends in predictability and the home field advantage has been vanishing ubiquitously. This is a first attempt to study football at a large scale and within a historical framework.